INFLUENCE OF SILUMIN DEOXIDIZER-MODIFIER ON THE STRUCTURE OF STEEL INGOTS - V. Ju. Stetsenko; A. P. Gutev; V. V. Novikov (Литьë и металлургия)
It is shown that introduction of structural-superfine silumin deoxidizer-modifier allows to decrease the quantity of input into liquid steel lump and tribe-hardware deoxidizers more than by 30%, to reduce the defects of ingots by liquating stripes half, to reduce the content of sulphur in steel by 11–26% and of phosphorus by 12–42% and also to grind the steel grade 2–8 times as much.